The intertwining of vocational aptitude and interest: A study among university students in Indonesia - Fatuhrahmah, Ufi; Darusmin, Dian Fithriwati; Widiana, Herlina Siwi (Research and Social Study Institute, 2020)
Vocational aptitude and interest are the fundamental factors that education and career counselors utilize to provide suggestions to clients. These concepts are often considered as separate constructs. However, aptitude and interest are interrelated and should both be considered when making career decisions. This study involved as many as 343 university students as participants. Two measurement tools were used: Employee Aptitude Survey (EAS) to measure aptitude and Self-Directed Search (SDS) Holland to measure vocational interest. The data were analyzed using canonical and Pearson product-moment correlation analysis. The findings show that there is a correlation between several types of interest and several types of aptitude. Vocational interest that has the strongest correlation with aptitude was the investigative interest, while the numerical aptitude test has the strongest correlation with interest. In the process of career decision-making, particularly for university students, both aptitude and interest must be taken into consideration, especially the investigative interest and numerical aptitude.